Associations of somatic cell count with milk yield and reproductive performance in grazing dairy cows - Rearte, Ramiro (2022)
Poor udder health status can have a detrimental effect on milk yield and reproductive performance, leading to reductions in the dairy farm profit. The objective of this retrospective longitudinal study was to assess the associations of somatic cell count (SCC) with daily milk yield and reproductive performance. A database with 1,930,376 lactations from 867 Argentinean grazing dairy herds records collected for 14 years was used. The association of the evolution of SCC (healthy vs. new case vs. cured vs. chronic; with 150,000 SCC/mL as threshold) and of the severity of SCC [mild (150,000–400,000 SCC/mL) vs. moderate (400,000–1,000,000 SCC/mL) vs. severe (>1,000,000 SCC/mL)] with the odds for conception were estimated. Finally, the associations of the linear score of SCC (LS-SCC) with daily milk yield were estimated depending on parity and milk production quartile. The odds ratios (CI 95%) for conception at first service were 0.921 (0.902–0.941), 0.866 (0.848–0.884), and 0.842 (0.826–0.859) for the new case, cured, and chronic cows compared with healthy cows, respectively. Also, the odds ratios (CI 95%) for conception were 0.902 (0.881–0.925), 0.837 (0.808–0.866) and 0.709 (0.683–0.736) for mild, moderate and severe cases compared with healthy cows, respectively. An increase of one point of LS-SCC was associated with decreases of 0.349, 0.539, and 0.676 kg in daily milk yield for first-, second-, and third-lactation cows, respectively. In conclusion, SCC is negatively associated with the risk for conception and with daily milk yield in grazing dairy cows. This negative relationship with conception is higher when SCC increase occurs after the service date and it is influenced by severity of mastitis, and in the case of milk yield, the negative association is influenced by parity, milk production quartile, and severity of mastitis.